Ciprofloxacin-Induced Crystal Nephropathy and Allergic Interstitial Nephritis: Case Report and Review of Literature - Parthav Shah; Marci Chock; Yoshito Nishimura; Carmen Say; Kimberly Teehera; Rick Hayashi; Lisa Kim (Annals of Internal Medicine: Clinical Cases)
Ciprofloxacin is a commonly used antibiotic that has the potential to cause acute kidney injury (AKI) secondary to interstitial injury or vasculitis. Of all causes, allergic interstitial nephritis is the most common of ciprofloxacin-induced AKI. There have been very few case reports of crystal nephropathy resulting from ciprofloxacin. Most patients with crystal nephropathy respond well to conservative management, but some require hemodialysis and glucocorticoids treatment. We describe a patient case of a 67-year-old woman who developed AKI secondary to ciprofloxacin-induced crystal nephropathy and allergic interstitial nephritis who was successfully managed with hemodialysis and a short course of glucocorticoids.